Basel violations, volatility model variants and value at risk: Optimization of performance deviations in banks - Anjum, Shahid (Economics and Business Letters, 2021)
Basel penalties originate from VaR violations where a bank may end up either holding more capital or will risk to be reverted to standardized approach. Regulatory capital charge can have a huge impact on banks’ profitability which depends on the estimation of VaR thresholds which is evaluated by the approaches like hypothesis tests, back-testing procedures and Basel Accord regulatory calculations for penalty zones are used. A multi-criteria performance measure has been introduced in this study in order to select the optimal internal model based on performance evaluation techniques which could possibly help in reduction in the VaR violations and thus may leave more capital with banks.